Development of Flood Disaster Model through PAIC Process - Mongkonsin, Cherdpong; Thiengkamol, Nongnapas; Thiengkamol, Tanarat (Richtmann Publishing, 2013)
The integrative research was done with participatory action research with Participatory Appreciate-Influence-Control technique(PAIC) and qualitative research with focus group discussion. The sample was selected according to purposive samplingtechnique. The PAIC was implemented with 38 community leaders who came from community that faced with flood disaster in2011 from Kuntarawichai District in Mahasarakham Province with brain storming integrated in focus group discussion duringthe training process. During training, Three Dimensional Evaluation (TDE) covers Self-evaluation, Friend-evaluation, andFacilitator-evaluation. One -Way-ANOVA, and Paired t-test were used for data analysis. The research results illustrated thatbefore and after PAIC process implemented the posttest mean scores of knowledge of environmental education principle,natural disaster from flood disaster, flood response behavior and training achievement score were higher than pretest withstatistical significance (p< .01, p< .01, p< .01, and p< .01). Three Dimensional Evaluations were employed for determinationthe perceptions of 38 community leaders in three aspects evaluation covering Self-evaluation, Friend-evaluation, andFacilitator-evaluation by using One-way ANOVA in order to investigate the participation of peoples and the result showed thatthere were no difference of mean scores for participation in training process in past, present and future situations withstatistical significance (p>.05, p>.05, and p>.05). Moreover, supervising, monitoring, and evaluating for flood responsebehaviors, it was found that the community leaders set plan and hold meeting with community peoples to implement project forlife safety with preparation of communication equipment, boat, food, water, drug, and place for living including establishing thecommittee for surveillance, warning, and support from involved work unit. Moreover they hold program of disaster exercise tomove to safety place at good and very good levels in all aspects.